Caught in Translation: Studies on Versions of Late-Antique Christian Literature - Toca, Madalina,; Batovici, Dan, (Texts and Studies in Eastern Christianity ;, 2020)
Ancient translations of late antique Christian literature serve to spread the body of knowledge to wider audiences in often radically new cultural contexts. For the texts which are translated, their versions are not only sometimes crucial textual witnesses, but also important testimonies of independent strands of reception, cast in the cultural context of the new language. This volume gathers ten contributions that deal with translations into Latin, Syriac, Armenian, Georgian, Coptic, Old Nubian, Old Slavonic, Sogdian, Arabic and Ethiopic, set in dialog in order to highlight the range of problems and approaches involved in dealing with the reception of Christian literature across the various languages in which it was transmitted.